The modern Epimetheus: Carl Schmitt's katechontism as reactionary chronopolitics - Falk, Hjalmar (Frontiers in Political Science, 2022)
This paper deals with the reactionary form of chronopolitics that characterizes the work of the German jurist, political theorist, and radical conservative intellectual Carl Schmitt (1888–1985). Called both the latest classic of political thought and the Crown Jurist of the Third Reich, Schmitt remains a controversial figure, not least because of his practical support of the Nazi regime and his authoritarianism. Another controversial aspect of Schmitt's work are his unabashed and outspoken references to theology as a resource for legal and political thought. Many commentators regard Schmitt's support for the Nazi regime, his general authoritarianism, and his recourse to theology as expressions of an apocalyptic worldview that is taken to form the basis for his alleged decisionism. This in turn matches an analysis of twentieth-century totalitarianisms as constituting innerworldly forms of radical millenarian faith. However, the structure of Schmitt's politico-theological reason should be understood in a very different way. Rather than affirming the apocalyptic and millenarian energies of totalitarian movements, Schmitt attempted to formulate a theory aimed at containing them and averting their revolutionary fervor in defense of the state. At the heart of this endeavor was the Biblical figure of the katechon, “the restrainer” of the Antichrist and lawlessness as described in the Second Letter to the Thessalonians. Focusing particularly on a short but dense essay published in 1950, the paper lays bare the basis for Schmitt's avertive apocalypticism, or katechontism, which can be regarded as the politico-theological emblem of what Schmitt himself in contrast to decisionism described as concrete order thinking. The form of reactionary chronopolitics Schmitt expresses there is analyzed with the help of theories of modern historical temporality and contextualized through his own references to contemporary conservative thinkers like Hans Freyer, Karl Löwith, and Konrad Weiss.